Meera Atkinson. The Poetics of Transgenerational Trauma. Bloomsbury, 2017. - Katie Lally (Studies in 20th & 21st Century Literature, 2018)
Review of Meera Atkinson. The Poetics of Transgenerational Trauma. Bloomsbury, 2017.
Keywords: Trauma; Literary Theory; Women and Gender Studies; Feminist Theory; Creative Critical Writing